Religious Education and Moral Development: The influence of a religious childhood on moral orientation and competence - Akin, Asli (ETHICS IN PROGRESS, 2019)
The previous moral psychological research on educational institutions highlighted the influence on the development of moral orientation and competence. With the help of the present quantitative study, the influence of early childhood education on moral abilities has been explored. Since the moral education of children is often associated with religious norms and values, and religions are debated in relation to their general meaning and functionality, the religious moral education has been investigated. Therefore, students of various disciplines from Berlin were asked about their religious education in their early childhood and were examined on their current moral orientation and competence. The Moral-Competence-Test by Lind and a self-constructed and piloted questionnaire for the examination of religious education and religiosity have been used for the measurement. The results of the online study have shown that the moral skills of dogmatically educated students are significantly reduced, but not related to the differences in educational experience or the current preservation of religiousness.